Pengaruh Brand Image, Kualitas Produk Dan After Sales Service Terhadap Keputusan Pembelian - Hendy Novendra Pratama; Mulyono Mulyono; Muchlis Mas’ud (FEB Universitas Maritim Semarang, 2023)
This study aims to determine the effect of brand image, product quality and after-sales service on purchasing decisions at U Winfly Malang electric bike. This study used a quantitative approach, totaling 60 consumers on U Winfly Malang electric bike who were selected by total sampling and saturated sample techniques as research subjects. The statistical analysis used in this study is with the help of the SmartPLS version 3.9 computer program. The results showed that brand image had a significant positive effect on purchasing decisions, product quality had a significant positive effect on purchasing decisions, After sales service had no significant positive effect on purchasing decisions at U Winfly electric bicycles Malang